Lanthanides and Actinides in Molecular Magnetism. Edited by Richard A. Layfield and Muralee Murugesu. Issue 51 (6th November 2015) - Powell, Annie
Abstract : Wiley‐VCH, Weinheim, 2015. 346 pp., hardcover, € 139.00.—ISBN 978‐3527335268